A química no ensino fundamental : uma proposta investigativa e contextualizada - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The Investigative Teaching Sequence is an important way to facilitate and raise the students 'level of learning and should be planned based on the content of the school schedule, promoting an environment in which students' knowledge is valued. For elementary school, the sequence becomes even more relevant, since most students have difficulties, mainly in content related to Chemistry. The objective of this work was to promote, through an Investigative Teaching Sequence, the contextualization of the contents related to the teaching of Chemistry for 6th grade students of Elementary School, evaluating criteria such as scientific perception and knowledge about Science and Chemistry. For this, na Investigative Teaching Sequence was elaborated addressing the theme of separating mixtures within the context of the immune system and food allergies. The activity was applied in a class of 6th year of Elementary School and made it possible to discuss current issues such as the importance of vaccination as a prophylactic measure, it allowed to recall what primary colors are and how secondary and tertiary colors are formed. The activity allowed students to understand different techniques for separating mixtures and, after carrying out an experiment, apply the chromatography technique to separate pigments. Questionnaires were applied before and after conducting the investigative activity and the answers were grouped into categories to facilitate the interpretation of differences before and after the activity. Many students did not clearly understand what Chemistry is, nor did they understand its presence in everyday life. In addition, many students stated, in the questionnaire before the activity was applied, that for different reasons they did not participate in the discussions during classes. Throughout the application of the activity, it was possible to observe the increase in student participation and interaction among themselves and between students and researcher. It is possible to state that SEI made it possible for these students to be introduced to an idea of what Chemistry is and even though there was a change in some concepts of students who had a stereotyped view of both Chemistry and its applications and the type of work performed by a Chemist. The essay performed here demonstrates that such activities are important for the teaching-learning process and can be used in different situations, however, such methodologies do not work if they are applied in isolation or out of context with other content, and must be planned by teachers and the educational institution's pedagogical team.
Keywords: Ensino por Investigação; Experimentação; Ensino Fundamental; Ensino de Química; Investigative Teaching Sequence; Experimentation; Elementary School; Chemistry teaching; ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS EXATAS E DA TERRA::QUIMICA